Heating rate effects on thermal analysis measurement of Tg in composite materials. (3rd April 2017) - Yong, Ana X. H.; Sims, Graham D.; Gnaniah, Samuel J. P.; Ogin, Stephen L.; Smith, Paul A.
Abstract: Three measurement techniques used to measure the glass transition temperature ( T g ) have been subjected to a critical comparison; dynamic mechanical analysis (DMA), thermomechanical analysis, and differential scanning calorimetry. A new procedure, whereby different specimens are tested over a range of heating rates, has been used in order to eliminate the effects of thermal lag and determine a T g independent of heating rate ( T g (0) ). It has been shown that for measurements of T g (0) for composites, the DMA thermal lag "corrected" method gave the most reliable data. The work has provided additional guidance on these techniques that could usefully be incorporated in future standards, to improve precision, comparisons, and consistency of T g measurement. Abstract :